Perancangan Sistem Informasi Pendataan Swab Pegawai Pada PT. Perkebunan Nusantara III - Nasution, Annisa; Muhathir, Muhathir (Universitas Medan Area, 2024)
PT. Perkebunan Nusantara III is an Indonesian state-owned enterprise engaged in the plantation sector. However, since the Covid-19 pandemic, the company has required all PTPN employees to carry out swabs to prevent transmission of Covid-19. Prior to conducting employee swabs, there is data collection first. Currently, swab data collection at PTPN III still uses the manual method, namely using paper as a document. Therefore the purpose of this research is to design an Information System for Employee Swab Data Collection at PT. Perkebunan Nusantara III to replace the use of paper in processing employee swab data. By designing a swab data collection information system, it is hoped that it can reduce the use of paper and make it easier to collect employee swab data at PTPN III.